Diplomasi Ekonomi Indonesia dalam Meningkatkan Ekspor Produk Tekstil ke Australia melalui IA-CEPA Tahun 2020-2023 - Syifa Humaira Amani; Syahrul Salam (Andalas Institute of International Studies UNAND, 2024)
This research aims to analyze the economic diplomacy strategy carried out by Indonesia to export textile products, especially apparel, to Australia through the Indonesia Australia Comprehensive Economic Partnership Agreements (IA-CEPA) for 2020-2023. In this research, the method used is a descriptive method using interviews and literature study. The research results show that although the overall export trend shows positive results, there has been no significant change in exports of Indonesian textile products since IA-CEPA was implemented. This happens because there are still trade challenges both internal and external. The economic diplomacy carried out by the Indonesian Government is not only to overcome these challenges but also to encourage increased exports of Indonesian textile products to Australia. Economic diplomacy is analyzed based on Kishan S. Rana's theory which consists of four stages, namely economic salesmanship, networking, image building, and regulation management. Economic diplomacy is carried out through exhibitions, network expansion, information dissemination, promotions digital, and accelerated implementation of IA-CEPA with a memorandum of understanding and issuing Minister of Trade Regulation No. 36 of 2023 concerning Import Policies and Regulations to protect the domestic textile industry.